Team based learning: an effective teaching-learning method in undergraduate teaching in community medicine - D., Thirunaaukarasu; E., Karthikeyan; Norman, Prasan; M., Geetha; Felicia, Princz; J., Tejas (International Journal Of Community Medicine And Public Health, 2024)
Background: “Team-based learning (TBL)” is a special approach by using small groups that is student centered, teacher guided Teaching and Learning method. Medical Council of India (MCI) emphasizes small group teaching. With increasing student numbers and decreasing/no change in faculty strength, the need for an effective T-L method for incorporating small group teaching in a large group is essential. So, this study attempts to evaluate the effectiveness and student reaction for TBL. Methods: A cross sectional study was conducted among III-year MBBS students attending block posting in the Department of Community Medicine, KIMS and RC. Pre-test and post-test after Team based learning implementation by designated faculties was conducted, and scores were analysed. The feedback of TBL was collected by using a Likert scale from students and also from faculties. Results: The mean scores of pre- and post-test were analyzed by Paired T test which was statistically significant (p value <0.05). The student reaction evaluated by 7 items Likert scale questionnaire showed that most of the students either agreed or strongly agreed that TBL enhanced their learning experience and confidence. The faculty feedback about TBL was also positive. Conclusions: TBL can be effectively implemented in medical colleges for the better results and student reaction.